Stopping Sight Distance and Available Sight Distance: New Model and Reliability Analysis Comparison. Issue 1 (2017) - Wood, Jonathan S.; Donnell, Eric T.
Stopping sight distance (SSD) is an important design criterion used in the geometry of highways and streets. Design guidance implies that SSD is used to ensure safety along the roadway. This paper reviews SSD design criteria and develops an updated model to improve consistency between available sight distance and SSD criteria found in geometric design policy. A new variable, the distance from the front of the car to the driver's eye ( L front-eye ), is used in the updated model. Distributional values for L front-eye are determined. A method accounting for lighted (daytime and lighted nighttime) versus unlighted nighttime conditions is also discussed. A probabilistic analysis of vertical curve SSD uses Monte Carlo simulation. The results of this analysis are compared with the SSD model found in current geometric design policy. Possible values for L front-eye that can be used in design guidance are proposed. Potential issues that should be investigated in future work are discussed.